The Circular RNA Profiles of Colorectal Tumor Metastatic Cells - Jiang, Weiqin; Zhang, Xingchen; Chu, Qinjie; Lu, Sen; Zhou, Linfu; Lu, Xingang; Liu, Chen; Mao, Lingfeng; Ye, Chuyu; Timko, Michael P.; Fan, Longjiang; Ju, Haixing (Frontiers in Genetics, 2018)
Circular RNAs (circRNAs) have been reported that can be used as biomarkers for colorectal cancers (CRC) and other types of tumors. However, a limited number of studies have been performed investigating the potential role of circRNAs in tumor metastasis. Here, we examined the circRNAs in two CRC cell lines (a primary tumor cell SW480 and its metastasis cell SW620), and found a large set of circRNA (2,919 ncDECs) with significantly differential expression patterns relative to normal cells (NCM460). In addition, we uncovered a set of 623 pmDECs that differ between the primary CRC cells and its metastasis cells. Both differentially expressed circRNA (DEC) sets contain many previously unknown putative CRC-related circRNAs, thereby providing many new circRNAs as candidate biomarkers for CRC development and metastasis. These studies are the first large-scale identification of metastasis-related circRNAs for CRC and provide valuable candidate biomarkers for diagnostic and a starting point for additional investigations of CRC metastasis.